The Effectiveness of Inside-Outside Circle Method by Using Cue Card for Students’ Speaking Ability at Seventh Graders: Keefektifan Metode Inside-Outside Circle dengan Menggunakan Cue Card untuk Kemampuan Berbicara Siswa Kelas Tujuh - Wijaya, Armeria; Sudrajad, Mochammad (Universitas Muhammadiyah Sidoarjo, 2016)
As far as the researcher’s knowledge, the analysis of “The Effectiveness of Inside-Outside Circle Method by Using Cue Card for Students’ Speaking Ability” is still difficult to find, the researcher formulates the statement of the research, Inside-Outside Circle method is effective for student’s speaking ability. The objective of research is to find out whether Inside-Outside Circle method can be effectively for students’ speaking ability. This research uses experimental design. The subject are 7B grade as experimental group and 7C as controlled group at SMP Muhammadiyah 11 Surabaya, this sample is taken by snowball sampling. The data collection uses test (pre-test and post-test) as intrument to measure the result of students. The results of the research will be counted using T-test statistic with